Math Anxiety: Past Research, Promising Interventions, and a New Interpretation Framework. Issue 3 (3rd July 2018) - Ramirez, Gerardo; Shaw, Stacy T.; Maloney, Erin A.
Abstract : Mathematics anxiety is a pervasive issue in education that requires attention from both educators and researchers to help students reach their full academic potential. This review provides an overview of past research that has investigated the association between math anxiety and math achievement, factors that can cause math anxiety, characteristics of students that can increase their susceptibility to math anxiety, and efforts that educators can take to remedy math anxiety. We also derive a new Interpretation Account of math anxiety, which we use to argue the importance of understanding appraisal processes in the development and treatment of math anxiety. In conclusion, gaps in the literature are reviewed in addition to suggestions for future research that can help improve the field's understanding of this important issue.